Tourette's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The prevalence of Gilles de la Tourette's syndrome (TS) in school children from Monroe County, New York, was examined in the Depts of Psychiatry, Neurology and Pediatrics, University of Rochester Medical Center, Rochester, NY.